3D system-in-package design using stacked silicon submount technology. Issue 2 (5th May 2015) - Dong, Mingzhi; Santagata, Fabio; Sokolovskij, Robert; Wei, Jia; Yuan, Cadmus; Zhang, Guoqi
Abstract : Purpose: – This study aims to provide a flexible and cost-effective solution of 3D heterogeneous integration for applications such as micro-electro-mechanical system (MEMS) applications and smart sensor systems. Design/methodology/approach: – A novel 3D system-in-package (SiP) based on stacked silicon submount technology was successfully developed and well-demonstrated by the fabrication and assembly process of a selected smart lighting module. Findings: – The stacked module consists of multiple layers of silicon submounts which can be designed and fabricated in parallel. The bonding and interconnecting process is quite simple and does not require complicated equipment. The 3D stacking design offers higher silicon efficiency and miniaturized package form factor. The submount wafer can be assembled and tested at the wafer level, thus reducing the cost and improving the yield. Research limitations/implications: – The embedding design presented in this paper is applicable for modules with limited number of passives. When it comes to cases with more passive devices, new process needs to be developed to achieve fast, inexpensive and reliable assembly. Originality/value: – The presented 3D SiP design is novel for applications such as smart lighting, Internet of Things, MEMS systems, etc.